An out-of-season cold: filler-induced vascular occlusion of the columellar artery causing necrosis of the cartilaginous anterior nasal septum case report and a literature review - Corrado Zengarini; Claudia Sapigni; Mattia Benati; Giovanni D'Agostino; Bianca Maria Piraccini; Davide Melandri; Antonio Russo; Società Italiana di Dermatologia Chirurgica, Oncologica, Correttiva ed Estetica (SIDCO) (PAGEPress Publications, 2024)
In their recent publication, George Kroumpouzos et al. provided a comprehensive update on the complications caused by filler procedures in the lips and perioral area. These injections have been associated with various arterial accidents and an incidence of vision loss mainly when such procedures are performed at the level of the central facial massif. Among the various cases of vascular involvement reported in the literature, we have found what we believe to be a rare occurrence of columellar artery occlusion with a noteworthy discrepancy between the expected symptoms and the actual described vascular effects. The necrosis of the columellar artery following hyaluronic acid injections showed some peculiarities: its frequency is unknown, and recognition can be troublesome due to the presentation of subtle symptoms. We want to exemplify these characteristics in this case, which, fortunately, optimally resolved itself, underscoring its unique nature.